HUMAN RESOURCE ANALYTICS AND DECISION-MAKING EFFECTIVENESS: A CONCEPTUAL REVIEW - Mochammad Isa Anshori; Ayunda Pradini; Ulfa Aulia (CV. Lafadz Jaya, 2026)
The development of digital transformation in human resource management has encouraged organizations to utilize Human Resource Analytics (HRA) as a basis for more effective, data-driven decision-making. This study aims to analyze the role of Human Resource Analytics in improving the effectiveness of organizational decision-making through a literature review approach. The research method used is a literature review by collecting, reviewing, and analyzing various scientific sources in the form of national and international journals, academic books, and other scientific publications relevant to the topic of Human Resource Analytics and decision-making effectiveness. The results of the study indicate that the implementation of Human Resource Analytics can help organizations identify employee behavior patterns, improve the efficiency of the recruitment process, predict workforce performance and retention, and support the development of more accurate and objective organizational strategies. In addition, the use of human resource analytics also contributes to improving the quality of managerial decisions through the use of real-time data and predictive approaches. However, the implementation of Human Resource Analytics still faces various challenges, such as limited data quality, low human resource analytical competency, and issues of employee data ethics and privacy. This study concludes that Human Resource Analytics has a strategic role in improving the effectiveness of organizational decision-making in the digital era. Therefore, strengthening analytical competency and integrated data management are necessary for its optimal implementation.